An Engineered Fusion Protein Anti-CD19(Fab)-LDM Effectively Inhibits ADR-Resistant B Cell Lymphoma - Fan, Dongmei; Jiang, Linlin; Song, Yuewen; Bao, Shiqi; Yang, Yuanyuan; Yuan, Xiangfei; Zhen, Yongsu; Yang, Ming; Xiong, Dongsheng (Frontiers in Oncology, 2019)
The five-year survival rate of patients with B cell lymphoma is about 50% after initial diagnosis, mainly because of resistance to chemotherapy. Hence, it is necessary to understand the mechanism of chemo-resistance and to explore novel methods to circumvent multidrug resistance. Previously, we showed that an engineered cytotoxic fusion protein anti-CD19(Fab)-LDM (lidamycin), can induce apoptosis of B-lymphoma cells. Herein, we successfully established an adriamycin (ADR)-resistant B cell lymphoma cell line BJAB/ADR. The mRNA and protein level of ATP-binding cassette subfamily B member 1 (ABCB1) were significantly overexpressed in BJAB/ADR cells. Increased efflux function of ABCB1 was observed by analyzing intracellular accumulation and efflux of Rhodamine 123. The efflux of Rhodamine 123 could be significantly ameliorated by verapamil. Treatment with anti-CD19(Fab)-LDM at different concentrations induced cytotoxic response of BJAB/ADR cells similar to that of the sensitive cells. In vivo studies showed that anti-CD19(Fab)-LDM had better antitumor effect in BJAB and BJAB/ADR cell lymphoma xenografts compared with ADR or LDM treatment alone. Taken together, anti-CD19(Fab)-LDM can effectively inhibit the growth of BJAB/ADR cells both in vitro and in vivo. Anti-CD19(Fab)-LDM could be a promising molecule for the treatment of drug resistant cancers.